STRATEGI MENINGKATKAN KUALITAS KELUARGA SAKINAH DI KAMPUNG PENTAS DESA SAKAMBANG PURWAKARTA - Ash Shabah, Musyaffa Amin; Hambali, Yoyo; Supriyanto, Agus; -, Suprihatin (LPPM Universitas Islam 45 Bekasi, 2021)
Fostering a sakinah family is the dream of all people who are building a household, efforts to make it happen is not an easy matter, because it requires hard work and support from all parties in the family, both father, mother and child. Not a few families who have problems and even fail in the middle of the road, because some family members do not have a sense of responsibility and do not carry out their obligations as they should in the family. For this reason, marriage guidance is needed as a preventive measure so that there are no disputes in the household. The implementation method in this activity is counseling to the community directly with resource persons in accordance with their fields. The results of this activity indicate an increase in public awareness of the importance of building and implementing a sakinah family in their respective families.